PEMANFAATAN CANVA AI DALAM PENDAMPINGAN PENYUSUNAN PERANGKAT PEMBELAJARAN BERBASIS DEEP LEARNING TEMATIK ANTI-BULLYING DI SEKOLAH DASAR - Nurna Listya Purnamasari; Eka Yuliana Sari (Adiba Aisha Amira, 2026)
21st-century education demands a transformation in the development of teaching materials so that they are not merely administrative documents, but effective pedagogical strategies. This Community Service (PkM) activity aims to provide guidance to teachers at SDI Al Ishlah Tulungagung in developing teaching materials based on the deep learning approach using Canva AI technology. The implementation of the PkM involved 20 teachers and was carried out through four main stages: preparation, implementation, programme evaluation, and reporting, all of which were conducted using a participatory approach. The results of the activity demonstrated a significant improvement in participants’ understanding and skills, with the average teacher understanding score rising from 74.4% in the pre-test to 80.3% in the post-test. The teachers successfully applied Canva AI to design deep learning teaching materials, particularly those addressing crucial themes such as education and the handling of bullying within the school environment. This activity not only enhanced educators’ digital literacy but also strengthened their capacity to design meaningful, problem-solving-based learning environments.